2006
DOI: 10.1128/iai.00687-06
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses to Lung-Stage Helminth Infection Induce Alternatively Activated Alveolar Macrophages

Abstract: While it is well established that infection with the rodent hookworm Nippostrongylus brasiliensis induces a strongly polarized Th2 immune response, little is known about the innate host-parasite interactions that lead to the development of this robust Th2 immunity. We exploited the transient pulmonary phase of N. brasiliensis development to study the innate immune responses induced by this helminth parasite in wild-type (WT) and severe-combined immune deficient (SCID) BALB/c mice. Histological analysis demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 84 publications
7
143
2
1
Order By: Relevance
“…day 70+). These data are at odds to the conclusions drawn by Reece et al [19], who reported that mechanical damage and hemorrhaging are rapidly resolved following Nb infection. Indeed, the early innate response and massive hemorrhaging that occurs immediately following Nb infection is largely resolved within 12 days, however, they did not examine later time points.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…day 70+). These data are at odds to the conclusions drawn by Reece et al [19], who reported that mechanical damage and hemorrhaging are rapidly resolved following Nb infection. Indeed, the early innate response and massive hemorrhaging that occurs immediately following Nb infection is largely resolved within 12 days, however, they did not examine later time points.…”
Section: Discussioncontrasting
confidence: 59%
“…Alternative macrophage activation is driven primarily through the presence of IL-4 although IL-13 and IL-21 have also been implicated in their differentiation [20,21]. Infection by Nb induces a strong Th2 immune response and is known to activate alternative macrophages [19]; however, their long-term presence in the airways suggests that additional mechanisms flowing on from the original infection may sustain their renewal and differentiation. Notably, microarray analysis of lungs from smokeinduced emphysema [22] show a similar pattern of gene expression to that described here; specifically, the upregulation of alternatively activated macrophage markers including FIZZ, YM1, and AMcase and the protease MMP-12.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rapid increases of AAMΦs are detected in the lung by 4 days after N. brasiliensis infection in SCID mice lacking T cells, and this increase is associated with elevated Ym1, FIZZ1/RELMα, and arginase-1. After day 4, however, expression of these genes decreases markedly in the lungs of N. brasiliensis-infected SCID but not in infected WT mice [4], suggesting that innate cells may make sufficient IL-4/IL-13 to induce initial differentiation of AAMΦs, but that Th2 cells are required to sustain their activity. Mice infected with the cestode T. crassiceps and subsequently co-infected with either of two protozoan species of Leishmania exhibit a potent Th2-type response without downregulating IFN-γ levels; nevertheless, the protective response to Leishmania is blocked and disease exacerbated.…”
Section: Alternative Activation Of Macrophagesmentioning
confidence: 97%
“…AAMΦs are observed in a variety of helminth infections, including Th2-type immune responses to Schistosoma mansoni [2], Heligmosomoides polygyrus [3], Nippostrongylus brasiliensis [4], Taenia crassiceps [5], Trichinella spiralis [6], Fasciola hepatica [7], Ascaris suum [8], and filarial parasites [9]. A number of markers are used to identify AAMΦs ( Figure 1).…”
Section: Characterization and Phenotypementioning
confidence: 99%
“…Surgeries were performed as described previously [13]. In short, animals were anesthetized with 300 mg/kg body weight with Avertin (2,2,2-tribromoethanol, Acros Organics, Morris Plains, NJ, USA), administered i.p.…”
Section: Bronchial Alveolar Lavage (Bal)mentioning
confidence: 99%